Identification of SSR markers linked to Botrytis grey mould resistance in chickpea (Cicer arietinum) - Sachdeva, Supriya; Dawar, Shruti; Rani, Upasana; Patil, Basavanagouda Siddanagouda; Soren, Khela Ram; Singh, Sarvjeet; Sanwal, Satish Kumar; Chauhan, Sanjeev K.; Bharadwaj, Chellapilla (Phytopathologia Mediterranea, 2019)
Botrytis grey mould (BGM), caused by Botrytis cinerea, is emerging as an important disease of chickpea in the northern and eastern parts of the Indian Subcontinent, including Nepal, Bangladesh, Pakistan, and in Australia. This fungus has a very broad host range, and sources of complete resistance to the disease have not been found in Cicer arietinum L. germplasm. Resistance to this pathogen has been identified in some wild Cicer species. A set of 371 lines, including 164 landraces and 207 interspecific derivative lines (derived from crosses of cultivated chickpea with C. pinnatifidum, C. judaicum or C. reticulatum) have been screened against Botrytis grey mould under field conditions, and using the cut twig method at the Punjab Agricultural University (PAU), Ludhiana, in 2015-16 and 2016–17. Strong correlations between the two screening methods were indicated by paired-t tests. The Bulked Sample Analysis (BSA) approach was used to screen DNA of the five most resistant and five most susceptible host lines using 300 simple sequence repeat (SSR) markers. Eighty-eight markers were polymorphic. Chi-square statistic values showed strong correlations of TA144, GA102, TA194, TA140 and TR2 with the resistant bulks, signifying their usability as putative markers linked to BGM resistance, and for development of BGM tolerant genotypes in chickpea. Future studies should rapidly ascertain marker trait associations, and identify and develop diagnostic markers that provide an accurate method of molecular tagging BGM resistant genes in chickpea.